Disclosing medical information through social networks: The legal repercussions - Jahn Kassim, Puteri Nemie (On İki Levha Yayincilik A. Ş., 2019)
Social networks have been considerably beneficial for medical practitioners in interacting with relevant stakeholders particularly, in ensuring efficient continuity of care and enhancing research studies. Nevertheless, the discussions on patients’ information over social networks have triggered a myriad of legal issues particularly, relating to the law on confidentiality, defamation and privacy rights. Thus, it has become increasingly vital for medical practitioners to be aware of the related legal risks and extremely cautious in deciding what information they are able to share on their social networking sites so as not to compromise their professionalism, ethical duties as well as the required legal standards. Further, in view of the vulnerabilities of such digital information, healthcare providers as employers should enact policies with appropriate guidelines to ensure that their employees are aware of the legal risks of posting confidential information on social networks and understanding the need to ensure integrity in professional communications. By employing qualitative research methods, this paper seeks to discuss the importance of medical confidentiality in the digital age from the ethical as well as legal perspectives and analysing the legal repercussions of breaching medical confidentiality through social networks. Addressing the arising legal repercussions and privacy concerns will ultimately ensure a safe and effective environment in the modern healthcare setting.